2010
DOI: 10.1063/1.3462316
|View full text |Cite
|
Sign up to set email alerts
|

Impact of solid-phase crystallization of amorphous silicon on the chemical structure of the buried Si/ZnO thin film solar cell interface

Abstract: ͑͒The chemical interface structure between phosphorus-doped hydrogenated amorphous silicon and aluminum-doped zinc oxide thin films is investigated with soft x-ray emission spectroscopy ͑XES͒ before and after solid-phase crystallization ͑SPC͒ at 600°C. In addition to the expected SPC-induced phase transition from amorphous to polycrystalline silicon, our XES data indicates a pronounced chemical interaction at the buried Si/ZnO interface. In particular, we find an SPC-enhanced formation of Si-O bonds and the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…However, it has been reported elsewhere that already after solid phase crystallization at 600 C, corresponding to the "no RTA" results shown here, the formation of Si-O bonds and the accumulation of Zn in close proximity to the interface occurs. 21 With increasing RTA-temperature, the shape of the curve is more and more fitting to the Zn 2 SiO 4 -spectrum illustrating the modification of the chemical bonding of the Zn close to the interface. The integration of a SiN barrier layer between poly-Si and ZnO:Al has no considerable influence on this behavior (grey curves in Fig.…”
Section: B Microstructural Propertiesmentioning
confidence: 96%
See 1 more Smart Citation
“…However, it has been reported elsewhere that already after solid phase crystallization at 600 C, corresponding to the "no RTA" results shown here, the formation of Si-O bonds and the accumulation of Zn in close proximity to the interface occurs. 21 With increasing RTA-temperature, the shape of the curve is more and more fitting to the Zn 2 SiO 4 -spectrum illustrating the modification of the chemical bonding of the Zn close to the interface. The integration of a SiN barrier layer between poly-Si and ZnO:Al has no considerable influence on this behavior (grey curves in Fig.…”
Section: B Microstructural Propertiesmentioning
confidence: 96%
“…Synchrotron based X-ray spectrometry is an emerging method for the non-destructive investigation of diffusion and the determination of the chemical species at buried interfaces of stacked thin layers, because of which it is particularly suited for the characterization of high-temperature processes in complex thin-film solar cell devices. [21][22][23] Here, we applied grazing incidence X-ray fluorescence combined with near edge X-ray absorption fine structure spectroscopy (GIXRF-NEXAFS) 24 at the Plane Grating Monochromator (PGM) beamline for undulator radiation 25 in the PTB laboratory at BESSY II for the analysis of buried ZnO:Al/poly-Si interfaces after high-temperature RTA processing.…”
mentioning
confidence: 99%
“…Nevertheless, it was observed that the electrical properties of the ZnO:Al improved due to the heat treatment. 4 First, x-ray spectroscopy experiments 6,7 indeed indicate that the SPC treatment has an impact on the chemical Si/ZnO interface structure, but could not completely clarify the underlying reaction mechanism. In this letter, we employ photoemission and its unique capability in chemical speciation combined with hard x-ray excitation allowing for the study of relevant buried Si/ZnO interfaces i.e., the Si top layer is sufficiently thick to form the same interface structure as present in a real-world Si thin-film solar cell layer stack.…”
mentioning
confidence: 99%
“…These findings are in good agreement with results of our earlier studies. 7 In order to shed more light on the chemical structure of the Si/ZnO interface and how it changes upon SPC annealing, we analyze the Si 1s and O 1s spectra at hm ¼ 6030 eV in more detail (Fig. 3).…”
mentioning
confidence: 99%
“…Note that both thin Si samples exhibit a higher Si-O x contribution, presumably due to the higher surface/bulk ratio and, potentially, the previously observed oxidation at the Si/ZnO:Al interface. 6,33,34 The IIBB is determined by subtracting the binding energy difference between the core levels of the capping layer and the substrate of the thin silicon sample [e.g., E Si 2s Fig. 4.…”
mentioning
confidence: 99%